Planowanie marketingowe i controlling marketingowy - modele integrujące zarządzanie wartością przedsiębiorstwa - Rupik, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The paper attempts to identify the integrative role of marketing planning and controlling in the contemporary management. The author concerns the selected directions for the development of traditional models of both marketing planning and controlling basing on strategic business design (business models) theory. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 383-394